Gardens in Rural Areas of Mid-Mountain in Auvergne-Rhône-Alpes Region: Revealing a Relationship to Food in Recomposition - Noé Guiraud; Claire Delfosse; Perrine Vandenbroucke; Philomène Viricel; Laura Munar (Revue de Géographie Alpine)
Gardening and self-consumption practices face deep changes related to food transition in rural areas - the mountainous area Auvergne Rhône-Alpes region is no exception. Recent research about the role of gardens in daily consumption, mainly focuses on urban gardens. In this context, this paper aims to enlighten the role of gardens in food practices of the rural population living in intermediate areas of the mountain - the “mid-moutains”. It is based on research conducted as part of the Jardin’R project. We show that the garden is a gateway to individual and collective self-consumption practices in rural areas. Then we analyze the part these practices play in food policies conducted in our case studies. Finally, we show that reinvestment in self-consumption practices in rural mountains leads to their promotion as an element of the food heritage of these territories.